2014
DOI: 10.1016/j.bbadis.2014.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Thromboxane synthase expression and correlation with VEGF and angiogenesis in non-small cell lung cancer

Abstract: TXS promotes tumor growth in-vivo in NSCLC, an effect which is at least partly mediated through increased tumor angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…These observations indicate that thromboxane/TP signaling likely acted as an endogenous inhibitor of ASC differentiation toward ECs under (patho)physiological conditions. However, others reported that TP blockers suppressed migration and angiogenesis of human umbilical vein ECs and human dermal microvascular ECs, 44 TxAS overexpression observed in nonsmall cell lung cancers promotes tumor growth and VEGF secretion, 45,46 and activation of TP induced the differentiation of human ASCs to smooth muscle-like cells. 47,48 The discrepancies are probably ascribed to different cells and different approaches used, and perhaps different downstream signaling is mediated by TP receptors.…”
Section: Discussionmentioning
confidence: 99%
“…These observations indicate that thromboxane/TP signaling likely acted as an endogenous inhibitor of ASC differentiation toward ECs under (patho)physiological conditions. However, others reported that TP blockers suppressed migration and angiogenesis of human umbilical vein ECs and human dermal microvascular ECs, 44 TxAS overexpression observed in nonsmall cell lung cancers promotes tumor growth and VEGF secretion, 45,46 and activation of TP induced the differentiation of human ASCs to smooth muscle-like cells. 47,48 The discrepancies are probably ascribed to different cells and different approaches used, and perhaps different downstream signaling is mediated by TP receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that TxA 2 activated the TP signaling pathway, and promoted cell proliferation, survival, and invasion [77][78][79][80]. TP also promoted tumor growth and angiogenesis via induction of VEGF in A549 cells and NSCLC patients [81,82]. NNK's oncogenic mechanisms in lung cancer ( part I) NNK, the lung cancer carcinogen, activates several signaling pathways as follows: (i) NNK increases α7-nAChR-mediated expression of contactin 1, followed by activating RhoA and down-regulating E-cadherin, thereby promoting tumor invasion and metastasis.…”
Section: Nnk Regulates Gene Expression Through Dna Methyltransferase mentioning
confidence: 99%
“…Nonsmall cell lung cancer (NSCLC) is one of the most life‐threatening type of lung cancer, and its development and metastasis are closely related to angiogenesis . In addition, many investigations have shown that high Plt number was significantly associated with poor prognosis in patients with advanced NSCLC .…”
Section: Introductionmentioning
confidence: 99%